UPAYA MENINGKATKAN PEMBELAJARAN SEPAK BOLA MINI MELALUI PERMAINAN BOLA HOLAHOP PADA SISWA KELAS V SD NEGERI 01 BOJONGBATA KECAMATAN PEMALANG KABUPATEN PEMALANG TAHUN AJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
This study aims to improve learning outcomes through the mini soccer ball game holahop the fifth gradestudents of SD Negeri 01 Bojongbata District Pemalang of Pemalang Regency academic year 2012/2013.This study uses action research. The subjects of this study were fifth grade students of SD Negeri 01 BojongbataDistrict Pemalang of Pemalang Regency academic year 2012/2013 a total of 39 students made up of 13 boysand 26 student daughter. Physical education teacher and our partners in this role as an observer or observersduring the learning takes place, while the researchers themselves implementing learning or as guru.Obyek thisresearch is learning through play mini soccer ball holahop. Data collection techniques used observation andtest.Proved from 39 students in the student activity prasiklus, cycle I cycle II was increased to kick the ball atprasiklus score of 2.50 obtained in the first cycle increased to 2.58 and the second cycle increased to 3.64.Prasiklus dribble on scores obtained in the first cycle increased 2.00 to 2.44 and the second cycle increased to3.50. Prasiklus puts the ball on the score obtained in the first cycle increased 2.25 to 2.53 and the second cycleincreased to 3.36. Total activity score obtained by the students at prasiklus 6.75, in the first cycle increased to7.55 and the second cycle increased to 10.50. The average score on prasiklus obtained 2.25 which includes the unfavorable category, in the first cycle increased to 2.52 which includes the unfavorable category and the second cycle increased to 3.50 which includes both categories.Conclusions: This study indicates that the approach can improve the game ball holahop mini soccer skills at the fifth grade students of SD Negeri 01 Bojongbata District Pemalang of Pemalang Regency academic year 2012/2013,